Adhesive hydrogel with anti-inflammatory, antioxidant and pro-angiogenic capabilities and its application
By developing a three-layer adhesion hydrogel with anti-inflammatory, antioxidant and provascularization capabilities, the problem of insufficient bionic ability of stent materials in the treatment of myocardial infarction is solved, and effective repair and functional recovery of myocardial tissue is achieved.
Patent Information
- Application Number
- CN202410628361.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-05-21
AI Technical Summary
In the treatment of myocardial infarction, the bionic ability of the scaffold material is insufficient, the constructed myocardial tissue is incomplete, the developmental pattern of myocardial tissue is unclear, and the effect of myocardial infarction repair is poor.
An adhesion hydrogel with anti-inflammatory, antioxidant and provascularization capabilities was developed, including an anti-adhesion layer, an adhesion layer and an inner layer, formed by cross-linking of ACG solutions at different pH values. The inner layer is loaded with EGCG-coated DEX-PBAP liposomes, which can firmly adhere to the wound and release the active ingredients.
This hydrogel can effectively absorb wound exudate, reduce inflammatory response, promote cell adhesion and blood vessel formation, improve the survival rate of implanted cells, reduce the infarction area, and is suitable for repair of myocardial injury tissue.
Smart Images

Figure CN118576766B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomaterial preparation, and in particular to an adhesive hydrogel with anti-inflammatory, anti-oxidation and angiogenesis-promoting capabilities and application thereof. Background Art
[0002] Cardiovascular disease (CVD) is one of the leading causes of death worldwide, and most deaths are caused by myocardial infarction (MI) and its related heart failure (HF). After MI, the myocardium undergoes an inflammatory phase, a proliferative phase, and a remodeling phase. The complex pathological changes in each phase lead to significant changes in the myocardial microenvironment, including the disruption of the dynamic balance of oxygen / blood, reactive oxygen species (ROS), inflammatory factors, and matrix metalloproteinases (MMPs), which in turn cause massive myocardial cell death, inflammatory response, extracellular matrix degradation, and myocardial fibrosis. In order to reverse this staged malignant biological change and rebuild the function of the infarcted myocardium, it is urgent to develop a new therapeutic strategy that can promote myocardial repair in order to achieve effective treatment of MI. Currently, the effective methods for treating myocardial infarction are left ventricular assist devices and heart transplantation; however, the former is limited by the long-term reliance on external devices and the latter is limited by the severe lack of donated organs, and both methods require invasive and inherently high-risk surgeries. In recent years, with the continuous breakthroughs in the research of stem cells, biomaterials and biomanufacturing engineering, myocardial tissue engineering has been trying to overcome the limitations of therapeutic substances by utilizing biomaterials to protect the delivered therapeutics from loss or degradation, reduce side effects, improve bioavailability, and increase the passive targeting of the delivered substances. It is considered to be a potential treatment for myocardial infarction.
[0003] As one of the important components of cardiac tissue engineering, biomaterials play an extremely important role in the construction of engineered cardiac tissues (ECTs) in vitro and the repair of damaged myocardium in vivo. Their performance directly affects the quality of ECTs and the effect of MI repair. Therefore, the development of biomaterials that effectively simulate the structure and microenvironment characteristics of natural myocardial tissue is crucial for cardiac tissue engineering research. Although traditional MI treatment methods, including minimally invasive interventional therapy and drug therapy, have shown positive effects such as improving cardiac function and prolonging patient life expectancy, there are still problems such as irreversible progressive myocardial necrosis or decreased cardiac function. In addition, since 2005, the American "Popular Science" proposed that ECTs transplantation and repair of myocardial infarction sites based on the Band-Aid strategy is expected to provide new therapeutic techniques and strategies for the treatment of heart diseases. However, the current effect of ECTs transplantation based on the Band-Aid strategy for myocardial infarction is still not ideal. There are problems such as insufficient biomimetic ability of scaffold materials, incomplete function of constructed myocardial tissue, unclear development rules of myocardial tissue, and poor repair effect of myocardial infarction. Summary of the invention
[0004] In order to solve the above problems, the present invention has developed an adhesive hydrogel with anti-inflammatory, antioxidant and pro-angiogenic capabilities. The hydrogel has a short gel time, does not require the addition of additional cross-linking agents during the gelation process, can firmly adhere to the wound, can absorb wound exudate to a certain extent, and does not produce toxic degradation products.
[0005] The first aspect of the present invention provides an adhesive hydrogel with anti-inflammatory, anti-oxidative and pro-angiogenic capabilities, comprising an anti-adhesion layer, an adhesion layer and an inner layer arranged in sequence;
[0006] The anti-adhesion layer and the adhesion layer are respectively formed by cross-linking ACG solutions with different pH values;
[0007] The inner layer uses methacrylated whey protein as a base material and is loaded with EGCG-coated DEX-PBAP liposomes, namely EGCG@DEX-PBAP.
[0008] Among them, the anti-adhesion layer prevents external tissue adhesion, and the adhesion layer can firmly adhere to the skin surface, playing a role similar to that of a band-aid. The active ingredients in the inner hydrogel are released to play a role, clearing excess ROS in the wound site, reducing inflammatory reactions, and promoting cell adhesion. The present invention uses N-acryloyl-2-glycine (ACG) as the anti-adhesion layer and the adhesion layer. ACG is a glycine-modified product, which is a smart hydrogel with pH responsiveness, high strength, and good biocompatibility. According to the different functions of the anti-adhesion layer and the adhesion layer, the requirements for swelling properties and adhesion properties are different, and the pH of the ACG solution can be regulated to form a corresponding gel. The EGCG@DEX-PBAP formed by the EGCG (epigallocatechin gallate)-coated liposome DEX-PBAP is a ROS-responsive liposome, which can be loaded into the inner base hydrogel as a bioactive ingredient, and has anti-inflammatory, antioxidant and pro-angiogenic capabilities.
[0009] In some embodiments, the ACG of the anti-adhesion layer and the adhesion layer is synthesized by the following method: sodium glycine is dissolved in a 6M NaOH solution and stirred and dispersed evenly in an ice bath, and then a tetrahydrofuran solution of acryloyl chloride is added dropwise. After the addition is completed, the ice bath is continued, and then water is added, washed with ether, the pH of the aqueous phase is adjusted to 2, and then NaCl is added to saturate, and finally extracted with ethyl acetate several times. After drying and concentration, the obtained product is dissolved in water and freeze-dried to obtain the ACG.
[0010] Preferably, sodium glycinate: 6M NaOH: acryloyl chloride: tetrahydrofuran = 5 g: 25 ml: 5.5 ml: 10 ml.
[0011] Preferably, the anti-adhesion layer is formed by cross-linking ACG solutions with different pH values of 7.0±0.5; and the adhesion layer is formed by cross-linking ACG solutions with pH values of 3-4.
[0012] Preferably, the ACG concentration in the ACG solution of the anti-adhesion layer and the adhesion layer is 15%.
[0013] In some embodiments, the methacrylated whey protein is synthesized by the following method: at 25-30°C, whey protein isolate is dissolved in phosphate buffered saline, and then methacrylic anhydride is added to adjust the pH to 8, the reaction is stirred and the pH is maintained at 8, dialyzed, frozen, and freeze-dried to obtain the methacrylated whey protein.
[0014] Preferably, the phosphate buffered saline is 1x phosphate buffered saline.
[0015] Preferably, whey protein isolate: phosphate buffered saline: methacrylic anhydride = 0.5 g: 9.5 ml: 0.1 ml.
[0016] In some embodiments, the particle size of the EGCG@DEX-PBAP liposome is 300-450 nm.
[0017] In some embodiments, the EGCG@DEX-PBAP liposomes are prepared by an ethanol injection method. Specifically, hydrogenated soybean phosphatidylcholine and cholesterol are dissolved in anhydrous ethanol, and DEX-PBAP is dissolved in anhydrous DMSO; then mixed to obtain a mixed solution; under high-speed stirring conditions, the mixed solution is added dropwise to the EGCG aqueous solution, and the ethanol is removed by rotary evaporation to obtain an EGCG@DEX-PBAP liposome solution.
[0018] Preferably, in terms of weight ratio, hydrogenated soybean phosphatidylcholine: cholesterol: DEX-PBAP: EGCG = 7.4: 16.7: 5.44: 12.
[0019] In some embodiments, the DEX-PBAP is prepared by the following method, comprising the steps of:
[0020] (1) dissolving 4-hydroxymethyl-phenylboronic acid pinacol ester and N,N'-carbonyldiimidazole in anhydrous dichloromethane for reaction, then adding ethyl acetate for dilution, followed by extraction with saturated NaCl, drying overnight, concentrating, and vacuum drying to obtain PBAP-CDI;
[0021] (2) Dissolve dextran in anhydrous dimethyl sulfoxide, add 4-dimethylaminopyridine, and then add the PBAP-CDI prepared in step (1), stir overnight, then precipitate the modified dextran in DH2O, separate the product by centrifugation, wash the obtained particles with dd-H2O, and remove the residual water by freeze drying to obtain DEX-PBAP liposomes.
[0022] Preferably, in step (1), the weight ratio of 4-hydroxymethyl-phenylboronic acid pinacol ester: N,N'-carbonyldiimidazole is 0.338:0.469.
[0023] Preferably, in step (2), the weight ratio of dextran:4-dimethylaminopyridine:PBAP-CDI is 90:149.3:364.6.
[0024] Preferably, the molecular weight of the dextran is 70000 g / mol.
[0025] In some embodiments, the hydrogel is a band-aid-like asymmetric adhesive hydrogel, which is more conducive to tissue modification, especially myocardial tissue.
[0026] In the adhesive hydrogel of the embodiment of the present invention, the crosslinking of each layer of gel material can be carried out by ultraviolet irradiation method, by photo crosslinking, and a photoinitiator can be added to the gel solution, and the photoinitiator can be lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP), etc. For example, in some embodiments, the hydrogel solutions of the anti-adhesion layer, the adhesion layer and the inner layer are all prepared with a concentration of 0.2% LAP solution as the solution.
[0027] Another aspect of the present invention provides the use of the above-mentioned adhesive hydrogel, which is suitable for repairing skin damage, muscle damage, nerve damage, and myocardial damage tissue.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The hydrogel of the present invention also has good anti-inflammatory, anti-oxidative and ROS elimination effects, and is particularly suitable for repairing damaged myocardial tissues. It can simultaneously improve the survival rate of implanted cells and induce neovascularization in ischemic myocardium, thereby reducing the infarct area.
[0030] 2. The raw materials of the hydrogel of the present invention can be prepared by modification, which is simple, cheap, safe and reliable;
[0031] 3. The hydrogel adhesive material of the present invention can be prepared into a composite hydrogel dressing by photo-crosslinking using ultraviolet light irradiation. The method is simple, the preparation is rapid, and no additional cross-linking reagents need to be added.
[0032] 4. The hydrogel prepared by the present invention has a short gelation time, can firmly adhere to the wound, can absorb wound exudate to a certain extent, does not produce toxic degradation products, has excellent mechanical properties, certain water absorption properties, controllable degradation properties, and excellent cell compatibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is an appearance morphology diagram of a three-layer adhesive hydrogel according to an embodiment of the present invention;
[0034] Figure 2 The liposome DLS particle size distribution test results; (A) particle size distribution of Example 2.4; (B) particle size distribution of Example 2.5;
[0035] Figure 3 Digital pictures of the adhesion of the three-layer adhesive hydrogel to plastic, glass, pig skin and steel according to the embodiment of the present invention;
[0036] Figure 4 The results of the EGCG release performance test; (A) the cumulative release rate of EGCG in Example 2.5 under different release conditions; (B) the cumulative release rate of EGCG in Example 2.7 under different release conditions;
[0037] Figure 5 The figures are the test results of the anti-inflammatory ability of the samples of the embodiments of the present invention. DETAILED DESCRIPTION
[0038] The following examples are used to further illustrate the present invention, but are not intended to limit the present invention. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. In addition, it should be understood that after reading the content of the present invention, a person skilled in the art in the field can make some non-essential improvements and adjustments based on the content of the present invention, and these equivalent forms also fall within the scope defined by the claims attached to the present application.
[0039] Unless otherwise specified, the reagents, materials, and equipment used in the examples of the present invention are all commercially available; for process parameters not specifically specified, conventional techniques can be used.
[0040] Example 1, raw material preparation:
[0041] 1.1 Synthesis of N-acryloyl-2-glycine (ACG)
[0042] Dissolve 5g of sodium glycinate (Gly) in 6M NaOH solution (25ml) and stir for 20min in an ice bath. Add 5.5ml of acryloyl chloride to 10ml of tetrahydrofuran (THF) c, stir and slowly add dropwise to the above solution for 2h, and continue ice bathing for 1h after the addition is complete. Add 10ml of water to the resulting solution, wash three times with ether to remove impurities, adjust the pH of the aqueous phase to 2, add NaCl to saturate, and finally extract with ethyl acetate several times. After drying and concentration, the obtained product is dissolved in 10ml of water and lyophilized to obtain ACG.
[0043] 1.2 Preparation of whey protein methacrylate (WPI-MA)
[0044] 0.5 g of whey protein isolate (WPI) was dissolved in 9.5 mL of 1x phosphate buffered saline (PBS) at 25-30°C, then 0.1 mL of methacrylic anhydride was added to the WPI solution, the pH was adjusted to 8 with 5 M NaOH, and the final volume was adjusted to 10 mL with PBS. Stir at 300 rpm for 24 h at 25-30°C, and the pH was maintained at 8. Subsequently, distilled water was dialyzed for 3 days with a 10 kDa cut-off dialysis bag. Finally, the WPI-MA solution was frozen at -80°C for 12 hours and freeze-dried for 24 hours to obtain WPI-MA.
[0045] 1.3 Preparation of liposome EGCG@DEX-PBAP
[0046] 1.3.1 Preparation of ROS-responsive liposomes DEX-PBAP
[0047] 0.338 g of 4-(hydroxymethyl)phenylboronic acid pinacol ester (PBAP) and 0.469 g of N,N'-carbonyldiimidazole (CDI) were dissolved in 46 mL of anhydrous dichloromethane (CH2Cl2). After reacting for 30 min, 100 mL of ethyl acetate was added for dilution, followed by extraction with saturated NaCl, drying over magnesium sulfate overnight, concentrating, and vacuum drying to obtain PBAP-CDI.
[0048] Dextran (DEX, molecular weight = 70000 g / mol, 90 mg) was dissolved in 1.575 mL of anhydrous dimethyl sulfoxide (DMSO). 149.3 mg of 4-dimethylaminopyridine (DMAP) was added, followed by 364.6 mg of PBAP-CDI, and stirred overnight. The modified dextran was then precipitated in DH2O (35 ml). The product was separated by centrifugation at 10000 rpm / 15 min, and the obtained particles were washed with dd-H2O (2 x 35 mL). The DEX-PBAP liposomes were obtained by removing the residual water by freeze drying.
[0049] 1.3.2 Preparation of liposome EGCG@DEX-PBAP by ethanol injection method.
[0050] First, 7.4 mg of hydrogenated soybean phosphatidylcholine (HSPC) and 16.7 mg of cholesterol (CHO-HP) were dissolved in 500 μL of anhydrous ethanol. Secondly, 5.44 mg of DEX-PBAP was dissolved in 200 μL of anhydrous DMSO and mixed with the above solution to obtain a mixed solution. At the same time, 12 mg of epigallocatechin gallate (EGCG) was weighed and dissolved in ultrapure water. Finally, under high-speed stirring conditions (400-800 rpm / min.), the mixed solution was added dropwise to the EGCG aqueous solution, and the ethanol was removed by rotary evaporation. Finally, the EGCG@DEX-PBAP liposome solution was obtained.
[0051] Example 2: Preparation of hydrogel and testing of liposome performance
[0052] The raw materials prepared in Example 1 were used to prepare a photoinitiator solution A, which was a 0.2% LAP solution; and each layer of hydrogel samples was prepared by cross-linking.
[0053] 2.1 Inner hydrogel——20% WPI-MA
[0054] The hydrogel described in this embodiment comprises the following steps:
[0055] 1. Use solution A as the dissolving solution to prepare a 20% WPI-MA solution;
[0056] 2. Pour the completely dissolved WPI-MA solution into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365nm wavelength ultraviolet light for 30s to complete the cross-linking of the hydrogel dressing, and demold to obtain the hydrogel dressing.
[0057] 2.2 Inner layer hydrogel——25% WPI-MA
[0058] The hydrogel described in this embodiment comprises the following steps:
[0059] 1. Use solution A as the dissolving liquid to prepare a 25% WPI-MA solution;
[0060] 2. Pour the completely dissolved WPI-MA solution into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365nm wavelength ultraviolet light for 30s to complete the cross-linking of the hydrogel dressing, and demold to obtain the hydrogel dressing.
[0061] 2.3 Inner layer hydrogel——30% WPI-MA
[0062] The hydrogel described in this embodiment comprises the following steps:
[0063] 1. Use solution A as the dissolving liquid to prepare a 30% WPI-MA solution;
[0064] 2. Pour the completely dissolved WPI-MA solution into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365nm wavelength ultraviolet light for 30s to complete the cross-linking of the hydrogel dressing, and demold to obtain the hydrogel dressing.
[0065] 2.4 3 mg / mL DEX-PBAP solution
[0066] EGCG@DEX-PBAP was prepared at a concentration of 3 mg / mL, and the particle size and anti-inflammatory ability were tested.
[0067] 2.5 3mg / mL EGCG@DEX-PBAP solution
[0068] EGCG@DEX-PBAP was prepared at a concentration of 3 mg / mL, and the particle size and anti-inflammatory ability were tested.
[0069] 2.6 Inner hydrogel——25% WPI-MA / DEX-PBAP
[0070] The hydrogel described in this embodiment comprises the following steps:
[0071] 1. Use solution A as the dissolving liquid to prepare a 25% WPI-MA solution;
[0072] 2. Ultrasonic dispersion of 3 mg / mL DEX-PBAP in WPI-MA solution;
[0073] 3. Pour the solution obtained in step 2 into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365 nm wavelength ultraviolet light for 30 seconds to complete the cross-linking of the hydrogel dressing, and demold to obtain the hydrogel dressing.
[0074] 2.7 Inner hydrogel——25% WPI-MA / EGCG@DEX-PBAP
[0075] The hydrogel described in this embodiment comprises the following steps:
[0076] 1. Use solution A as the dissolving liquid to prepare a 25% WPI-MA solution;
[0077] 2. Ultrasonic dispersion of 3 mg / mL EGCG@DEX-PBAP in WPI-MA solution;
[0078] 3. Pour the solution obtained in step 2 into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365 nm wavelength ultraviolet light for 30 seconds to complete the cross-linking of the hydrogel dressing, and demold to obtain the hydrogel dressing.
[0079] 2.8 Adhesion layer hydrogel——15% ACG (pH 3-4)
[0080] The hydrogel described in this embodiment comprises the following steps:
[0081] 1. Using solution A as the dissolving solution, prepare a 15% ACG solution (pH 3-4);
[0082] 2. Pour the completely dissolved ACG solution into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365nm wavelength ultraviolet light for 30s to complete the cross-linking of the hydrogel dressing, and demold to obtain the hydrogel dressing.
[0083] 2.9 Adhesion layer hydrogel - 20% ACG (pH 3-4)
[0084] The hydrogel described in this embodiment comprises the following steps:
[0085] 1. Using solution A as the dissolving solution, prepare a 20% ACG solution (pH 3-4);
[0086] 2. Pour the completely dissolved ACG solution into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365nm wavelength ultraviolet light for 30s to complete the cross-linking of the hydrogel dressing, and demold to obtain the hydrogel dressing.
[0087] 2.10 Adhesion layer hydrogel - 25% ACG (pH 3-4)
[0088] The hydrogel described in this embodiment comprises the following steps:
[0089] 1. Using solution A as the dissolving solution, prepare a 25% ACG solution (pH 3-4);
[0090] 2. Pour the completely dissolved ACG solution into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365nm wavelength ultraviolet light for 30s to complete the cross-linking of the hydrogel dressing, and demold to obtain the hydrogel dressing.
[0091] 2.11 Anti-adhesion layer hydrogel - 15% ACG (pH 7)
[0092] The hydrogel described in this embodiment comprises the following steps:
[0093] 1. Using solution A as the dissolving solution, prepare a 15% ACG solution (pH 7);
[0094] 2. Pour the completely dissolved ACG solution into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365nm wavelength ultraviolet light for 30s to complete the cross-linking of the hydrogel dressing, and demold to obtain the hydrogel dressing.
[0095] 2.12 Three-layer adhesive hydrogel
[0096] The hydrogel described in this embodiment comprises the following steps:
[0097] 1. Use solution A as the dissolving liquid to prepare a 25% WPI-MA solution, which is recorded as solution B;
[0098] 2. Using solution A as the dissolving liquid, prepare an ACG solution with a concentration of 15%, recorded as solution C;
[0099] 3. Use solution A as the dissolving liquid to prepare a 15% ACG solution, and use 1M NaOH to adjust the pH to about 7, which is recorded as solution D;
[0100] 4. Ultrasonic dispersion of 3 mg / mL EGCG@DEX-PBAP in solution B was recorded as solution E;
[0101] 5. Pour solution C into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365 nm ultraviolet light for 30 seconds to complete cross-linking of the hydrogel dressing, and demould to obtain the hydrogel anti-adhesion layer F;
[0102] 6. Pour solution D into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365 nm ultraviolet light for 30 seconds to complete cross-linking of the hydrogel dressing, and demould to obtain the hydrogel adhesion layer G;
[0103] 7. Pour solution E into the dressing mold, remove bubbles under a vacuum of -1 bar, irradiate with 365 nm ultraviolet light for 30 seconds to complete cross-linking of the hydrogel dressing, and demould to obtain the inner layer hydrogel H;
[0104] 8. After the hydrogel anti-adhesion layer F, the hydrogel adhesion layer G and the inner layer hydrogel H are formed, the hydrogel anti-adhesion layer F is placed in a culture dish, and the hydrogel adhesion layer G is evenly spread on F, and then the inner layer hydrogel H is placed on G to form a three-layer composite asymmetric adhesive hydrogel similar to a bandage.
[0105] 2.13 3mg / mL EGCG aqueous solution
[0106] An EGCG aqueous solution with a concentration of 3 mg / mL was prepared for anti-inflammatory ability testing.
[0107] 3. Performance Test
[0108] The performance of each gel and liposome in Example 2 was tested, and the results are as follows:
[0109] 3.1. Analysis of water absorption properties of each layer of hydrogel
[0110] Table 1 Water absorption test results
[0111]
[0112] Test method: Use the specific gravity method to accurately calculate the weight of liquid absorbed by a unit mass of wound dressing to obtain its water absorption rate. Soak the pre-weighed wound dressing sample in PBS solution at room temperature. After soaking for 10 minutes, use filter paper to absorb excess droplets on the surface of the sample and weigh it. The water absorption rate calculation formula is as follows:
[0113] m s (%) = (m1-m0) / m0×100%
[0114] Among them, m s -Water absorption rate, unit %; m0-initial mass of the sample, unit g; m1-mass of the sample fully absorbed by water, unit g.
[0115] Results: The samples of Example 2.4 and Example 2.5 are not gels, so the water absorption performance test was not performed.
[0116] Example 2.12 is a three-layer composite gel, so the experiment was designed to test the water absorption performance of each part separately.
[0117] The swelling rate is usually used to evaluate the liquid absorption capacity of the hydrogel, and the absorption of wound tissue fluid can prevent secondary bacterial infection. The high swelling rate of the hydrogel is closely related to hydrophilic functional groups such as -COO, -OH and -NH, which cause the hydrogel to absorb water and swell. The results in Table 1 show that the swelling rates of ACG hydrogels of different concentrations in deionized water gradually increase to varying degrees. This responsive water absorption behavior is attributed to the level of physical cross-linking. In addition, the change in the swelling rate of the inner layer WPI-MA shows that the basic change in the swelling rate of the WPI-MA hydrogel is not very obvious. In Example 2.3, rupture occurs during the swelling process. These observations prove that the entanglement between the molecular chains in the hydrogel is relatively tight. The important meaning of this is that the hydrogel can absorb wound exudate without causing the collapse of the cross-linked network and without squeezing the wound.
[0118] 3.2 Liposome particle size (DLS) analysis
[0119] Test method: The particle size distribution of the liposomes of Examples 2.4 and 2.5 was determined using dynamic light scattering.
[0120] Figure 2 Results: The particle size distribution of Example 2.4 and Example 2.5 was analyzed by dynamic light scattering. Figure 2 It can be seen that the particle size of Example 4 is 361.3 nm, and the particle size of Example 5 is 420.2 nm. EGCG as a drug is loaded into the ROS-responsive liposome DEX-PBAP, which increases its particle size distribution to a certain extent.
[0121] 3.3. Characterization of the appearance and morphology of the three-layer adhesive hydrogel
[0122] Figure 1 Appearance morphology of the three-layer adhesive hydrogel of Example 2.12.
[0123] Test method: After Example 2.12 is successfully prepared according to the above method, its appearance morphology is photographed.
[0124] Figure 1 Result description: From Figure 1 It can be seen that a three-layer composite asymmetric adhesive hydrogel similar to a bandage was prepared by UV curing and adhesion stacking. The prepared hydrogel is transparent + milky white in color and is more firmly adhered to the back of the hand. The inner layer WPI-MA is in direct contact with the wound, and the liposome EGCG@DEX-PBAP contained therein is released from the hydrogel to repair myocardial damage. Its outer layer has no adhesion effect and can protect other tissues and skin from damage.
[0125] 3.4 Adhesion performance
[0126] Test method: Take digital pictures of the adhesion of the anti-adhesion layer hydrogel of Example 2.11 to plastic, glass, pig skin and steel. Figure 3 shown.
[0127] The results show that an ideal wound dressing should provide a certain degree of adhesion, but should not adhere to the wound so much that it would damage the wound when torn off. Figure 3 It was found that the prepared hydrogel can adhere to the finger and wrist joints. Even after 90° bending, the hydrogel still remains in place at the joint. The adhesion of the anti-adhesion layer hydrogel of Example 2.11 was tested using objects of different materials. The pictures show that the hydrogel can adhere to various objects, including plastic, glass, steel and pig skin surfaces. Although the hydrogel can adhere to the skin, its adhesion is relatively weak and will not cause damage to the wound when torn.
[0128] 3.5. In vitro release properties of EGCG
[0129] Test method: In order to better examine the release kinetics model of EGCG in Example 2.5 and Example 2.7, 300 μL of Example 5 and 100 μL of Example 2.7 were placed in 5 mL PBS, respectively, and cultured in a constant temperature shaking incubator at 37°C and 100 rpm. At different time points (1, 3, 6, 24, 48, 72, 96, 120, 144, 168 h), 5 mL of PBS solution was taken and replaced with an equal amount of fresh PBS. The sample was centrifuged at 4000 rpm for 5 min. The absorbance of EGCG in PBS solution was measured using ultraviolet spectrophotometry at an excitation wavelength of 250 nm for tryptophan. At the same time, in order to simulate the active oxygen environment, the ROS group used a 1×10 -3 MH2O2 in PBS was used as the release solution. The remaining steps were the same as above. In addition, an EGCG standard curve was drawn: the EGCG solution was diluted by a two-fold dilution method, the absorbance values of different concentrations of EGCG at 250 nm were measured, and a standard curve was drawn for reverse calculation of the concentration of EGCG released in the dressing. Figure 4 (A) Cumulative release rate of EGCG in Example 2.5 under different release conditions; (B) Cumulative release rate of EGCG in Example 2.7 under different release conditions.
[0130] Results show that sustained release performance is an important indicator for evaluating the encapsulation performance of nanocarriers for active substances. Therefore, in vitro release experiments were conducted to study the release characteristics of EGCG in liposomes and hydrogels under different release conditions. Figure 4 In the same period of time, under the ROS environment, EGCG in liposomes and hydrogels showed a faster release rate.
[0131] 3.6 RAW264.7 cell culture and M1 induction culture
[0132] Test method: RAW264.7 at 1×10 6 The cells were inoculated at a density of 100 / well in a 24-well plate. After overnight culture, they were induced with 5 μg / mL LPS overnight. Then, the hydrogel extract / solution of different groups in Examples 2.1-2.13 was replaced. LPS and PBS were used as positive control group or negative control group, respectively, and cultured in an incubator overnight. Finally, the cells were fixed with 1% paraformaldehyde, washed with PBS, and CD86 and CD206 fluorescent antibodies were added respectively, and incubated at room temperature for 1 hour. After incubation, they were washed twice with PBS, and the percentages of M1 and M2 were observed by upflow cytometry.
[0133] Result description: The test results of each sample are as follows: Figure 5 As shown, by comparison, it can be seen that the ROS-responsive liposome EGCG@DEX-PBAP formed by encapsulating EGCG in the liposome DEX-PBAP can achieve a long-lasting sustained release effect after being loaded into the inner layer base hydrogel as a bioactive ingredient. At the same time, it can induce macrophage polarization from promoting inflammatory (M1) macrophages to anti-inflammatory (M2) macrophages, showing excellent anti-inflammatory ability.
[0134] From the above, it can be seen that the three-layer adhesion hydrogel of the embodiment of the present invention is cross-linked with ACG solutions of different pH layers to form an anti-adhesion layer and an adhesion layer, and the ROS-responsive liposome EGCG@DEX-PBAP formed by the EGCG-coated liposome DEX-PBAP is loaded into the inner base hydrogel as a bioactive component. Each layer of the obtained hydrogel has good performance, good adhesion, no tissue damage, good drug sustained release performance, good anti-inflammatory, antioxidant and ROS elimination effects, and is particularly suitable for myocardial damage tissue repair. It can simultaneously improve the survival rate of implanted cells and induce neovascularization in ischemic myocardium, reducing the infarct area.
[0135] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0136] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An adhesive hydrogel with anti-inflammatory, antioxidant and pro-angiogenic capabilities, characterized in that: It includes an anti-adhesion layer, an adhesion layer and an inner layer which are arranged in sequence; The anti-adhesion layer is formed by cross-linking an N-acryloyl-2-glycine solution at pH=7.0±0.5; the adhesion layer is formed by cross-linking an N-acryloyl-2-glycine solution at pH=3-4; the N-acryloyl-2-glycine is synthesized by the following method: Sodium glycinate is dissolved in a 6M NaOH solution and stirred in an ice bath to disperse evenly, then a tetrahydrofuran solution of acryloyl chloride is added dropwise, and the ice bath is continued after the addition is completed, and then water is added, washed with ether, the pH of the aqueous phase is adjusted to 2, and then NaCl is added to saturate, and finally extracted with ethyl acetate for several times, dried and concentrated, and the obtained product is dissolved in water, and freeze-dried to obtain the N-acryloyl-2-glycine; The inner layer uses methacrylated whey protein as a base material and is loaded with epigallocatechin gallate-coated dextran-4-(hydroxymethyl)phenylboronic acid pinacol ester liposomes; The methacrylate whey protein is synthesized by the following method: at 25-30° C., whey protein isolate is dissolved in phosphate buffered saline, then methacrylic anhydride is added, the pH is adjusted to 8, the reaction is stirred and the pH is maintained at 8, dialyzed, frozen, and freeze-dried to obtain the methacrylate whey protein; The preparation method of epigallocatechin gallate-coated dextran-4-(hydroxymethyl)phenylboronic acid pinacol ester liposome is as follows: hydrogenated soybean phosphatidylcholine and cholesterol are dissolved in anhydrous ethanol respectively, and dextran-4-(hydroxymethyl)phenylboronic acid pinacol ester liposome is dissolved in anhydrous dimethyl sulfoxide; then mixed to obtain a mixed solution; under high-speed stirring conditions, the mixed solution is added dropwise to the epigallocatechin gallate aqueous solution, and the ethanol is removed by rotary evaporation to obtain the epigallocatechin gallate-coated dextran-4-(hydroxymethyl)phenylboronic acid pinacol ester liposome solution; Wherein, the dextran-4-(hydroxymethyl)phenylboronic acid pinacol ester liposome is prepared by the following method, comprising the steps of: (1) dissolving 4-hydroxymethyl-phenylboronic acid pinacol ester and N,N'-carbonyldiimidazole in anhydrous dichloromethane for reaction, then adding ethyl acetate for dilution, followed by extraction with saturated NaCl, drying overnight, concentrating, and vacuum drying to obtain PBAP-CDI; (2) Dissolve dextran in anhydrous dimethyl sulfoxide, add 4-dimethylaminopyridine, and then add the PBAP-CDI prepared in step (1), stir overnight, then precipitate the modified dextran in DH2O, separate the product by centrifugation, wash the obtained particles with dd-H2O, and remove the residual water by freeze drying to obtain dextran-4-(hydroxymethyl)phenylboronic acid pinacol ester liposomes.
2. The adhesive hydrogel according to claim 1, characterized in that In the synthesis method of N-acryloyl-2-glycine, sodium glycinate: 6M NaOH: acryloyl chloride: tetrahydrofuran = 5g: 25ml: 5.5ml: 10ml.
3. The adhesive hydrogel according to claim 1, characterized in that In the method for synthesizing methacrylic acid whey protein, the phosphate buffered saline is 1 times phosphate buffered saline; whey protein isolate: phosphate buffered saline: methacrylic anhydride = 0.5 g: 9.5 ml: 0.1 ml.
4. The adhesive hydrogel according to claim 1, characterized in that The particle size of the dextran-4-(hydroxymethyl)phenylboronic acid pinacol ester liposome is 300-450nm.
5. The adhesive hydrogel according to claim 1, characterized in that In the preparation method of epigallocatechin gallate-coated dextran-4-(hydroxymethyl)phenylboronic acid pinacol liposomes, the weight ratio of hydrogenated soybean phosphatidylcholine: cholesterol: dextran-4-(hydroxymethyl)phenylboronic acid pinacol ester liposomes: epigallocatechin gallate is 7.4:16.7:5.44:
12.
6. The adhesive hydrogel according to claim 1, characterized in that In the preparation method of the dextran-4-(hydroxymethyl)phenylboronic acid pinacol ester liposome, In step (1), according to the weight ratio, 4-hydroxymethyl-phenylboronic acid pinacol ester: N,N'-carbonyldiimidazole: = 0.338: 0.469; In step (2), the weight ratio of dextran: 4-dimethylaminopyridine: PBAP-CDI is 90: 149.3: 364.6; The molecular weight of the dextran is 70000 g / mol.
7. The adhesive hydrogel according to claim 1, characterized in that The adhesive hydrogel is an asymmetric hydrogel in the shape of a band-aid.
8. The use of the adhesive hydrogel according to any one of claims 1 to 7, characterized in that: Suitable for repairing skin damage, muscle damage, nerve damage, and myocardial damage tissue.
Citation Information
Patent Citations
Degradable polymer hydrogel with adjustable mechanical properties and preparation method thereof
CN110938167A
Preparation and application of wet-state adhesive oral gel patch
CN113876741A